Akibat Hukum bagi Pekerja yang Tidak Mematuhi Employee branding Perusahaan Implikasi dan Tantangan dalam Lingkungan Kerja - Jemadur, Yohanes Brilian; Ambarwati, Mega Dewi (Jurnal Hukum Positum, 2024)
This study examines the legal consequences faced by employees who do not adhere to the principles of employee branding within companies. Employee branding is an important strategy that influences the image and reputation of organizations, as well as having a direct impact on the relationship between employees and the company. Through analysis of various cases and existing literature, this research identifies the legal ramifications that may arise from employee non-compliance, including breach of employment contracts, disciplinary actions, and potential reputational damage that could lead to legal claims. Additionally, this study explores the implications for employees regarding career development and professional responsibilities. Findings indicate that greater awareness and understanding of employee branding can help workers recognize the importance of their roles in building a positive corporate image. This research is expected to provide insights for companies in designing policies that support employee compliance with employee branding and mitigate potential legal risks.